The influence of typical versus atypical ads on sharing intention - Matos, Sara Filipa Lourenço de (2019)
The importance given to the growing levels of consumer´s brand engagement (CBE) is outstanding, because it is known that if a brand has a higher level of consumer brand engagement will also have great outcomes. Nevertheless, although engaging is considered one of the top priorities of the marketers, it still is a hard goal to achieve. Maybe one of the reasons why consumer engagement is still a difficult objective to achieve, is related to the fact that nowadays people are overwhelmed by the number of advertising campaigns. So, it is important for marketers understand what are the main characteristic that may turn a video ad campaign into a source of pleasure for consumers that will lead to a higher sharing intention. The experience conducted for this dissertation in an adequate laboratory with the use of consumers neuroscience methods, more specifically, eye tracking and Electrodermal activity (EDA), evaluated how typicality and the factor celebrity may influence consumer´s attention and Arousal. After, participants watched 4 scenarios of ad campaigns: Typical without celebrities (T); Typical with celebrities (TC); Atypical without celebrities (A) and Atypical with celebrities (AC), arousal and pleasure were also measured through the Self-Assessment Manikin and the sharing intention through questions on the final questionnaire. Findings demonstrate that atypical ads generate higher levels of arousal and pleasure, which positively influences sharing intention. Also, the factor celebrity when comparing (TC) with (A), presents lower levels of arousal in TC scenario. This leads to the conclusion that consumers want to be surprised and don´t want to feel that the advertising business is taking advantage of him, because if they feel that they are just watching another ad campaign they will not feel interesting to share that ad with others.